The Impacts of Extensive Agricultural Investment on Local Livelihood Income in Western Ethiopia - Ararso, Negatu; Wakweya, Rusha Begna (Indonesian Journal of Agricultural Research, 2024)
In western Ethiopia, large-scale agricultural investment has been growing, but its effects on local livelihood incomes have received less attention. This study investigates the impact of extensive agricultural investment on local livelihood incomes in Sibu Sire District, western Ethiopia. A total of 180 households were selected using simple random sampling. Descriptive statistics such as t-test, ANOVA, and Chi-square test were employed for data analysis. The results showed that there was a significant difference in household livelihood income prior-investment expansion among the three groups (F2, 178 = 17.41; P = 0.001), whereas there was no significant difference among the 3 groups post-investment expansion (F2, 177 = 0.9; P = 0.9). There was also no significant difference in social service provision among the groups. Regarding technology transmission, the respondents revealed that there was no significant difference among the groups. The study found that insiders (84.4%), outsiders (91.7%), and the control group (100.0%) had not introduced new technology. Moreover, crops and animal production by insiders and outsiders decreased compared to the control group. Therefore, the study suggests that the government needs to improve investment policy and make interventions to improve local socio-economic conditions in the area.